2023
DOI: 10.3390/membranes13040421
|View full text |Cite
|
Sign up to set email alerts
|

Ion Transport in Electromembrane Systems under the Passage of Direct Current: 1D Modelling Approaches

Abstract: For a theoretical analysis of mass transfer processes in electromembrane systems, the Nernst–Planck and Poisson equations (NPP) are generally used. In the case of 1D direct-current-mode modelling, a fixed potential (for example, zero) is set on one of the boundaries of the considered region, and on the other—a condition connecting the spatial derivative of the potential and the given current density. Therefore, in the approach based on the system of NPP equations, the accuracy of the solution is significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Aminat Uzdenova [ 2 ] proposes a new approach to the theoretical description of the direct current mode in electromembrane systems, which contain ion exchange membranes as well as diluted and enriched diffusion layers. The new approach does not require boundary conditions on the derivative of the potential drop.…”
mentioning
confidence: 99%
“…Aminat Uzdenova [ 2 ] proposes a new approach to the theoretical description of the direct current mode in electromembrane systems, which contain ion exchange membranes as well as diluted and enriched diffusion layers. The new approach does not require boundary conditions on the derivative of the potential drop.…”
mentioning
confidence: 99%
“…In recent work [56], based on the mathematical model in the form of the boundary value problem for the system of NPD equations, concentration profiles and electric field strengths were calculated in a depleted diffusion layer near the surface of an ion-exchange membrane, as well as in the cross-section of a desalination channel under the action of an overlimiting DC current. It was shown that this approach allows one to describe the formation of the extended SCR, as well as the approach based on the NPP equations.…”
mentioning
confidence: 99%
“…It was shown that this approach allows one to describe the formation of the extended SCR, as well as the approach based on the NPP equations. The equation for the displacement current contains only the time derivative and does not require the determination of boundary conditions [51,52,56]. In the equation for the displacement current, the small parameter stands at the time derivative of the electric field strengths.…”
mentioning
confidence: 99%
See 1 more Smart Citation